Efficiency of multinational banks: Impacts of geographic and product loci - Yildirim, C.; Kasman, A.; Gulamhussen, M. A. (International Business Review, 2023)
This paper explores geographic diversification strategies’ impact on multinational banks’ operational performance within the context of research on globalization and regionalization. We employ a sample of the 49 largest banks from 16 European countries from 2011 to 2018 and proxy operational performance by technical efficiency. We find the impact of geographic diversification on operational performance depends on the locus of geographic diversification—home-regional vs. inter-regional—and the interplay between geographic diversification and banks’ functional focus. More specifically, home-regional diversification together with a concentration on non-interest income-generating activities, including fee and commission and trading income, worsens performance, and diversification across regions alongside a focus on non-interest income-generating activities improves performance. Distinct product characteristics’ ability to facilitate different regional dispersions has important managerial implications for enhancing the success of geographic diversification strategies, a central but unresolved issue in global banking.